SELF MANAGEMENT IBU HAMIL YANG MENGALAMI HIPERTENSI DALAM KEHAMILAN - Hilmah Noviandry Rahman; Abdan Syakura; Wilda Inayah (Jurnal Kebidanan, 2024)
Hypertension in pregnancy is a major problem factor that contributes to the morbidity and mortality of pregnant women and fetuses in Indonesia. Further complications from hypertension should be handled by the self management of pregnant women so that their blood pressure remains normal. Research objective: the study was to determine the description of self management of pregnant women who experience hypertension in pregnancy. Research method: This type of research is descriptive quantitative, with a population of 3 trimester pregnant women who experience hypertension in pregnancy in the Banyuanyar Sampang Health Center working area in 2024 as many as 25 respondents with total sampling technique. Data collection was carried out by giving a questionnaire close anded scala likert self management of hypertension in pregnancy with data analysis using a range score, good = 76-100, enough = 51 = 75, and less = 25-50. Research results: Most of the respondents as many as 15 people (60%) had good self management and a small proportion of respondents as many as 3 people (12%) had poor self management in the Banyuanyar Sampang Health Center Working Area. Conclusion: Most of the self-management of pregnant women who experience hypertension in pregnancy in the good category, so respondents should work together in self-supervision during their pregnancy. Health workers coordinate in efforts to prevent unexpected possibilities by monitoring blood pressure during pregnancy until the delivery process.